The impact of vitamin D on the innate immune response to uropathogenic Escherichia coli during pregnancy. (May 2015) - Ramos, N.L.; Sekikubo, M.; Kironde, F.; Mirembe, F.; Sääf, M.; Brauner, A.
Abstract: Urinary tract infections are highly common during pregnancy, and can cause serious complications for the mother and baby. Vitamin D, predominantly obtained from the sunlight, is known to have an effect on the urothelium, with immunomodulatory capacity against Escherichia coli infection. However, its influence at this site remains to be further explored. This study therefore investigated its impact during pregnancy in a population of women who have the possibility of adequate year-round sun exposure. Serum from pregnant Ugandan women ( n = 32) in each trimester of pregnancy, from women after delivery ( n = 29) and from never-pregnant controls ( n = 25) was collected. 25-Hydroxyvitamin D (25-OHD), cathelicidin LL-37, human β-defensin 2, interleukin (IL)-8 and soluble CD14 serum concentrations were measured by chemiluminescence immunoassay or ELISA. The ability of serum to inhibit E. coli growth was tested. The immunomodulatory capacities of these serum samples and 1, 25-dihydroxyvitamin D3 were investigated in urothelial cells. Increases in 25-OHD and LL-37 levels were observed as pregnancy progressed, peaking in the third trimester. Serum 25-OHD levels were higher in multigravidae than in primigravidae, and correlated positively with maternal age. IL-8 levels were lower in the third trimester than in the first trimester, increased after delivery, but remained below those of never-pregnant women. Similarly, soluble CD14 concentrations increased after delivery. As gestation advanced, serum had an increased capacity to inhibit E. coli growth. In vitro, it modulated the IL-8 response to infection in a vitamin D concentration-dependent manner. Our findings demonstrate that increasing vitamin D levels as pregnancy advances modulate the innate immune system towards a protective response to infection.